Imagining America in 2033 : how the country put itself together after Bush - Gans, Herbert J. (University of Michigan Press, 2008)
In the spirit of great utopian writing that dares to hope for a better world, Imagining America in 2033 takes place in a fictional yet achievable future America--a time when progressive, liberal ideals inform politics and citizens alike. At the heart of Herbert J. Gans's utopian narrative is the vision of progress with fairness on which the best of American idealism has been built. Part utopia, part realism, Imagining America in 2033 is also a liberal's dream of life after Bush and a set of progressive yet practical guidelines for restoring sanity and intelligence to nearly every aspect of.